The Transformation of Malay Society in Pre-Colonial and Colonial Times: The Impact of Islam on Malay Education - A. Rahman Tang Abdullah (Dewan Bahasa dan Pustaka, 2016)
This article discusses Islam as the fundamental means in the transformation of Malay society during the pre-colonial and colonial periods. Historical analysis is employed to analyse the historical circumstances which influenced the continuity and changes taking place in Islamic education. The transformation of Malay society was shaped by Islam as a way of life. The main factors contributing to the process of transformation are literacy and education. According to history, the impact of knowledge and progressive values are only noticeable among the Malays after Islam had become the dominant religion in the Malay Archipelago in the 15th, 16th and 17th centuries. Though Islam had flourished as a religion, Islamic education did not reach the scale at which it could be labelled mass education until the late 19th century. This is due to the improvements made in Islamic institutions of learning as a result of the influence of modernity associated with a Western orientation. In this respect, it can be argued that a Western orientation helped to transform Islamic education into mass education, where literacy is concerned.